Fibromatosis in Maxillofacial Region: Case Report - Kundi, Jawad Ahmad; Khttak, Shahid Khan; Ali Shah, Syed Murad; Mannan, Amina Gul; Gul, Faryal (Journal of Gandhara Medical and Dental Science, 2015)
SUMMARY Fibromatosis is a rare and locally aggressive benign tumor arising from musculoaponeurotic structures. They are aggressive and tend to recur. Here we present a recurrent case of fibromatosis in a nineteen year old female focusing attention on the etiology, clinical presentation, pathology, various treatment options and modes of prevention of recurrence.